PENGARUH FAKTOR INTRA PERSONAL “SOCIAL ECOLOGICAL MODEL OF HEALTH BEHAVIOUR” TERHADAP PENURUNAN ANGKA KEMATIAN IBU (AKI) DI KABUPATEN KUPANG, NTT - INA DEBORA RATU LUDJI (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2014)
Maternal Mortality Rate (MMR) in the District of Kupang, NTT is still high.Therefore to accelerate reduction of the MMR a research was made with main objective to identify the influence of intra personal factor of ‘Social Ecological Model of Health Behaviour” which covered age, education, job, knowledge, attitude, intention, value and belief, self efficacy, distance, time travel and reproduction characteristics to the reduction of MMR with indicators K1, K4, delivery place, birthing assistant, post partum visit, and family planning in the District of Kupang. The type of research was observational analytic, cross sectional design with postpartu’s age to 3 months (126 women), analized with simple logistic regretion and double logistic regretion. The result of the research: The influence of Intra personal factor to pure K1 was contributed by job variable with OR 3.892; p = 0.027(Exp B=3.892; 95% CI: 1171 -12937. Attitude variable obtained OR 1.107 p = 0.004 ( Exp B = 1,107 ; 95% CI: 1,034 – 1,186). Value and bw variable obtained OR 1,202. p< 0,0001 ( Exp B = 1,202 ; 95% CI : 1,100 – 1,314). Influences of intrapersonal factor to K4 trimester 3: Job variable obtained OR 3,948. p = 0,013 ( Exp B = 3,984 ; 95% CI : 1,336 – 11,662). On the Attitude variable OR optained 1,086. p = 008 ( Exp B = 1,086 ; 95% CI : 1,022 – 1,155). Belief and Values vaiable obtained OR 1,156. p< 0,0001 ( Exp B = 1,156 ; 95% CI : 1,068 – 1,252). The influence of intrapersonal factor to birthing place. Knowledge variable obtained OR 1,022. p = 0,048 ( Exp B = 1,022 ; 95% CI : 1,000 – 1,045). Attitude variable obtained OR 1,038. p = 0,025 ( Exp B = 1,038 ; 95% CI : 1,005 – 1,073). Influence of intrapersonal factor to birthing assistant: Attitude variable obtained OR 1,075. p = 0,002 ( Exp B = 1,075 ; 95% CI : 1,027 – 1,126). Weight Gain variable obtained OR 1,219. p = 009 ( Exp B = 1,219 ; 95% CI : 1,050 – 1,414). Influence of intrapersonal factor to postpartum mothers obtained OR 1,063. p< 0,001 ( Exp B = 1,063 ; 95% CI : 1,026 – 1,101). Intention variable obtained OR 1,063. Influence of intrapersonal factor to family planning. Abortion variable obtained OR 0,416. p = 0,024 ( Exp B = 0,416 ; 95% CI : 0,194 –0,890). It is concluded that intrapersonal factor of “Social Ecological Model of Health Behaviour that influence the reduction of MMR in the District of Kupang, NTT was job, values and belief, attitude, knowledge, weight gain, intention and abortion.